2014
DOI: 10.1097/sap.0b013e31826eabfe
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Measurement of Wrist Motion Range Using the iPhone 4 Gyroscope Application

Abstract: The authors introduced a new method of measuring the range of wrist motion using the iPhone 4 Gyroscope application that is simpler to use and can be performed by the patient outside a clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 3 publications
3
55
0
Order By: Relevance
“…As far as the authors know, in only one study has wrist ROM been measured using a smartphone app (Gyroscope) and a universal goniometer (Kim et al 2014). The result of that study indicated that there was no statistically significant difference between the mean values of the iPhone â and universal goniometer (Kim et al 2014). However, to the best of the present authors' knowledge, no study has investigated the reliability and validity of smartphone apps for the measurements of wrist ROM.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…As far as the authors know, in only one study has wrist ROM been measured using a smartphone app (Gyroscope) and a universal goniometer (Kim et al 2014). The result of that study indicated that there was no statistically significant difference between the mean values of the iPhone â and universal goniometer (Kim et al 2014). However, to the best of the present authors' knowledge, no study has investigated the reliability and validity of smartphone apps for the measurements of wrist ROM.…”
Section: Introductionmentioning
confidence: 83%
“…A point worth mentioning is that the difference was not statistically significant and therefore did not have a negative influence or cause concerns to clinicians about the measurement of wrist ROM using the iPhone â app. Kim et al (2014) measured the ROM of the wrist using a universal goniometer and the iPhone â 4 Gyroscope app. The mean flexion-extension values of the universal goniometer were about 1°higher than the values obtained with the iPhone â app.…”
Section: Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…This technology is gaining increasing ground in clinical practice, as it constitutes a fast, accurate and easy-to-interpret tool [11,12,13,14,15]. Moreover, these applications can be used by patients themselves outside the clinical environment [16].…”
Section: Introductionmentioning
confidence: 99%